Analyzing the impact of investments in the agricultural sector on the macroeconomic indicators of the region using the VAR model - Badalov Dzhamshid Dzhamolovich (THE INNOVATION ECONOMY, 2026)
The article develops a VAR model to assess the impact of investments in agriculture on the macroeconomic indicators of the Surkhandarya region. Also, using this model, the forecast parameters of the regional GDP growth for 2025-2028 were calculated.